Hubungan Antara Ukuran Tumor dan Gradasi Histopatologi dengan Metastasis Kelenjar Getah Bening pada Penderita Kanker Payudara di RSUD Al-Ihsan Provinsi Jawa Barat - Rifky Riyadhi Akbar; Yusuf Heriady; Lisa Adhia G (Bandung Conference Series: Medical Science, 2022)
Abstract. Breast cancer is a malignancy that occurs in the epithelial tissue of the lobules or ducts of the breast glands. The majority of breast cancer patients come in an advanced stage, which impacts the patient's prognosis. The prognosis of breast cancer can be seen from various prognostic factors. This study aimed to analyze the relationship between tumor size and histopathological gradation with lymph node metastases in breast cancer patients. This cross-sectional study was conducted at Al-Ihsan Hospital, West Java Province on 76 patients. Data obtained from medical records in the form of histopathology lab results taken from January 2020 - December 2020. The data used univariate and bivariate tests. The results of the univariate statistical test showed that the characteristics of breast cancer patients were mostly T3 tumors, histopathological grade 3, and lymph node metastases were negative. The bivariate analysis results showed no relationship between tumor size (P=0.051) and histopathological gradation (P=0.912) with lymph node metastases. Abstrak. Kanker payudara merupakan keganasan yang terjadi pada jaringan epitel lobulus atau duktus dari kelenjar payudara. Mayoritas pasien kanker payudara datang dalam stadium lanjut yang memberikan dampak pada prognosis penderita. Prognosis kanker payudara dapat dilihat dari berbagai faktor prognostik. Tujuan penelitian ini untuk menganalisis hubungan antara ukuran tumor dan gradasi histopatologi dengan metastasis kelenjar getah bening pada penderita kanker payudara. Penelitian cross sectional ini dilakukan di RSUD Al-Ihsan Provinsi Jawa Barat pada 76 pasien. Data diperoleh dari medical record berupa hasil lab histopatologi yang diambil dari Januari 2020 – Desember 2020. Data menggunakan uji univariat dan bivariat Hasil uji statistik univariat didapatkan karakteristik pasien kanker payudara mayoritas berukuran tumor T3, berderajat histopatologi 3, dan metastasis kelenjar getah bening negatif. Hasil analisis bivariat didapatkan tidak terdapat hubungan antara ukuran tumor (P=0,051), dan gradasi histopatologi (P=0,912) dengan metastasis kelenjar getah bening.